ANALYSIS OF PUBLIC ACCEPTANCE OF E-GOVERNMENT SERVICES USING THE TAM MODEL (TECHNOLOGY ACCEPTANCE MODEL) - Pradana, Harrizki Arie; Salamat , Moh. Aizi Bin (MSJ : Majority Science Journal, 2025)
This study analyzes public acceptance of e-Government services in Indonesia using the Technology Acceptance Model (TAM), originally developed by Davis (1989), through a Systematic Literature Review (SLR) of national and international publications from 2015 to 2024. TAM positions Perceived Usefulness and Perceived Ease of Use as key drivers of technology adoption behavior, and in the context of public services, is further influenced by external variables such as trust and system quality. The findings show that Perceived Usefulness, Perceived Ease of Use, and Trust are consistently the dominant determinants of public acceptance of digital government platforms. Although adoption rates continue to increase, digital literacy gaps, access inequality, interface usability issues, and concerns over data security remain significant barriers. This study concludes that improving user experience, strengthening digital trust and cybersecurity, and enhancing digital inclusion programs are essential to ensuring sustainable e-Government adoption in Indonesia